Therapeutic Effect of Bicyclol Coupled with Aspirin Nanopreparation on Liver Function Damage Caused by Epstein-Barr Virus Infection in Children. (18th March 2022) - Yi, Wenxia; Zhang, Chunyan; Xu, Chunyan; Tian, Wenqiu; Xie, Fei; Yue, Bin
Abstract : The aim of study effective treatment is to reach the appropriate part of the body and then maintain the required drug concentration at sufficient intervals in order to achieve the clinical therapeutic effect. Problem of the Study . Biological barrier hinders the flow of most drugs from the blood to the focus. Methods of the Study . A novel nanopreparation for inhibition of Epstein-Barr virus (EBV) was developed based on poly (lactic-co-glycolic acid) (PLGA) nanodrug carriers loaded with bicyclic alcohol (BA) and aspirin (Asp) (PLGA-BA/Asp). Among them, the addition of PLGA can effectively improve the low solubility of BA and poor oral availability. Results have revealed that PLGA-BA/Asp is a multifunctional therapeutic drug that integrates antivirus, treatment of liver damage, and regulation of the immune system. This discovery provides a new treatment method for the treatment of liver injury in children with EBV infection.